THU0629 A study of wbmri in estimating disease activity of pm/dm and the following diseases diagnosis. (12th June 2018) - Li, Y.; Jiang, D.; Zheng, X.; Lu, L.; Li, Z.; Guo, Y.; Tang, J.; He, X.; Xu, D.; Gao, G.
Abstract : Background: IM is a group of disease characterised by chronic symmetrical myasthenia, muscle fatigue and monocyte infiltrating skeletal muscle. This disease usually associates with the muscle of trunk and proximal limbs, skin lesions companied or not. Dermatomyositis (DM) and polymyositis (PM) account for the major part of IM clinically. The diagnose of these diseases mainly rely on clinical manifestation, biopsy, ECG and serum creatase. Whole-body magnetic resonance imaging (WBMRI) has been reported succeeding in diagnosing PM/DM through short tau inversion recovery (STIR) sequence, but the ability to estimate disease activity hasn't been reported. Objectives: To evaluate the value in WBMRI through STIR sequence in evaluating the disease activity of polymyositis (PM) and dermatomyositis (DM) and screening interstitial lung disease (ILD) and osteonecrosis. Methods: PM/DM patients meeting the Bohan and Peter diagnostic criteria from the First Affiliated Hospital of Zhengzhou University were admitted between 2015 August to 2017 December. A retrospective analysis of the WBMRI imaging data, serum creatine kinase, electromyography and muscle biopsy were performed. The WBMRI images were estimated by semiquantitative score and the disease activity was estimated by MDAAT. SPSS 20.0 was utilised to analyse the statistical significance. Results: This study includes 61 patients, including 41 DM cases and 20 PM cases, all of these shows typical pathological feature and inflammatory muscle in WBMRI. Significant statistical correlation was found between the grade of muscle oedema estimated by WBMRI and the clinical assessment through MDAAT for muscle disease activity (DM r=0.57, p=0.006; PM r=0.84, p=0.001). The positive rate of serum creatine kinase test was 63% (39/61). Besides muscular changes, we also detected 35 cases in interstitial lung disease, 2 cases in osteonecrosis, 1 case in bone marrow oedema. Conclusions: WBMRI is a sensitive, noninvasive method to evaluate the disease activity, which is better than serum creatine kinase. And it is of great value to screen the complication or concomitant diseases such as ILD and osteonecrosis. References: [1] Elessawy SS, et al. Whole-body MRI for full assessment and characterization of diffuse inflammatory myopathy. Acta Radiol Open2016;5(9):2058460116668216.doi: 10.1111/j.1468–1331.2010.03012.x [2] Amato AA, Greenberg SA, Inflammatory myopathies. Continuum (Minneap Minn)2013;19(6 Muscle Disease): 1615–33. doi:10.1212/01.CON.0000440662.26427.bd [3] Tomasova SJ, et al. The role of MRI in the assessment of polymyositis and dermatomyositis. Rheumatology (Oxford)2007;46(7):1174–1179. doi:10.1093/rheumatology/kem088 [4] Andersson H, et al. Comparative analyses of muscle MRI and muscular function in anti-synthetase syndrome patients and matched controls: a cross-sectional study. Arthritis Res Ther2017;19(1):17. doi:10.1186/s13075-017-1219-y [5] Olsen NJ, Park JH. Inflammatory myopathies: issues in diagnosis and management. Arthritis Care Res1997;10(3):200–207. Disclosure of Interest: None declared